Who Needs Goals? A Case Study of a Goal-Free Evaluation - Brandon W. Youker; Alayna Zielinski; Ouen Hunter; Nicholas Bayer (Journal of MultiDisciplinary Evaluation)
Background: Goal-free evaluation (GFE) is any evaluation in which the evaluator conducts the evaluation without knowledge of or reference to predetermined goals and objectives whereas the goal-based evaluator determines merit according to the evaluand’s goal achievement.